Financiamento do saneamento básico no Brasil: A opç\~ao debêntures incentivadas - Gesmar Rosa dos Santos; Alesi Teixeira Mendes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This article's main objective is to present an overview of the financing of public basic sanitation services in Brazil. We emphasize incentivized debenture-type bond issues as a complement to traditional credit mechanisms for the sector, based on the database of debentures issued in Brazil, describing the categories and highlighted variables by infrastructure sector, in addition to the focus on drinking water and sanitation. The importance of debentures in the current set of financing sources for sanitation in Brazil is highlighted, even though the granting of incentives is recent in the country, starting in 2013, and increasing considerably since 2015, achieving the largest expansion in volume resources raised. However, there are doubts regarding the contribution of the focus on debentures to the universalization of drinking water and sanitation, since such financial securities are limited to large companies consolidated in the market and focus on water and sewage projects with good financial viability. Therefore, financing for other concessionaires and service holders continues to depend on other sources. In this scenario, the State must balance its efforts between the current focus, which is the waiver of taxes on debentures, and the allocation of public resources with a focus on the municipalities' deficit in the four components of Brazilian called "basic sanitation" services.
Keywords: G11; H54; Q25; 330; investments; debentures; sanitation; drinking water; infrastructure